The Level of Incentive System Among Banks Employees and Its Relation on Job Performance - Alshammari, Hammad (Archives of Business Research, 2023)
The aim of this study is to investigate the level of incentive system and its relation on job performance among banks employees. The study used the descriptive correlational approach where the sample consisted of (70) participants. The results of the study showed that the level of application of incentives, their importance, and their impact on the job performance of bank employees in the study sample came at a moderate level. The results of the study also showed that the level of application of incentives, their importance and impact on job performance came in favor of the general manager compared to the administrative employee and the head of the department. The results also showed that the level of application of incentives, their importance and their impact on job performance came in favor of those with less than 5 years of experience. Number of recommendations were suggested based on the above results.